Uma proposta de abordagem da matemática financeira no ensino médio - Marchioni, Aparecida Patrícia Roberto (2013)
This work intends to show the preparation and application of a Teaching Sequence on Mathematical Finance with two Middle School 3rd grade classes of a state school in São Paulo inland. The research methodology applied was Didactic Engineering. The study started by the research about the way Mathematical Finance was and is treated in Brazilian education, especially on the plans of São Paulo State, and about the knowledge of the two Middle School last grade classes on the subject. This work arose from the observations done, intending to relate the Mathematical Finance study with the mathematical concepts in the base, like the arithmetic and the geometric progressions and the increase factor, so avoiding the use of known by heart formulas, the most meaningless for the student. The proposed problems consist of current and fundamental applications for the student to analyze and make rational decisions in the product purchase options, as well as adherence to financing like that provided by the FIES (Student Financing Fund), highly publicized today.